ORGANOLOGICAL REVIEW OF ARI GUNADI'S CLASSIC GUITAR BRACING IN RANGKASBITUNG - Furqon, Aynan; Permana, Rian; Rizal, Syamsul; Purwinarti, Wiwin (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
Ari Gunadi, luthier from Rangkasbitung has been made classical guitar for years. He has problems, when he wants to make a good guitar, but only have cheap materials and tools. Ari realized that bracing is the most important part of the quality of a classical guitar. The aim of the study was to find out in detail about the organology of Ari Gunadi's bracing, and to find out the differences between Ari Gunadi's guitar bracing and similar bracing. The methodology used is descriptive qualitative by using observation, interviews, and literature as a medium for data collection. The research results obtained, that organologically Ari Gunadi used the